Events exposed : managing & designing special events - Malouf, Lena (John Wiley & Sons, 2012)
Features advice on operating a successful special events business, acquired from Malouf's more than forty years in the planning industry, and includes guidance on developing astrategy, identifying potential clients, developing proposals, building an event budget, coordinating with contractors, and much more